Influencer Driven Digital Marketing Communication and Its Impact on Consumer Trust and Engagement in the Construction Industry. - Estriana, Virna; Pratami, Rezki (Jurnal Ilmu Komunikasi, 2026)
This study examines digital marketing communication strategies based on content creators implemented by Ombilin Construction through Instagram and TikTok and their role in shaping consumer trust and engagement. The construction industry is commonly perceived as highly technical and less communicative, creating a gap in existing digital marketing research that predominantly focuses on consumer goods and lifestyle sectors. This study aims to address this gap by exploring how content creator–driven strategies operate within a construction services context. Employing a qualitative case study approach, data were collected through in-depth interviews with company management, content creators, and consumers, supported by systematic observation of social media content. Data analysis was conducted using NVivo software to identify dominant themes and relational patterns across informant groups. The findings reveal that Instagram functions as a curated visual showcase emphasizing portfolio presentation and professional credibility, while TikTok serves as a narrative-driven platform that highlights work processes and behind the scenes activities to expand audience reach. Content creators play a crucial intermediary role in translating technical messages into accessible and relatable visual narratives, thereby enhancing perceived authenticity. However, trust formation remains largely information oriented, relying on project outcomes and brief testimonials, with limited emphasis on value-based storytelling such as work standards, service transparency, and quality assurance mechanisms. Consumer engagement is reflected through likes, comments, and direct messages, yet remains underutilized in terms of participatory and interactive content strategies. The study concludes that content creator–based digital marketing communication holds strategic potential for professional service industries but requires deeper narrative integration to strengthen relational trust. Theoretically, this study extends digital marketing communication literature into the construction sector, while practically offering strategic insights for companies seeking to humanize technical services through social media engagement. Keywords: digital marketing communication, content creators, trust, consumer engagement, construction industry.